MOOD UNDERSTAND RECALL DIGEST EXPAND AND REVIEW STRATEGY FOR STUDENTS’ READING COMPREHENSION - Herlina Daddi; Dewi Susilawati; Andi Tenri Ampa; Amiruddin Amiruddin (Universitas Muhammadiyah Makassar, 2017)
This research aimed to explain the improvement of the students’ reading comprehension in terms of literal comprehension dealing with main ideas and sequence details and interpretive comprehension dealing with prediction outcomes and conclusion. To explain the improvement, the researcher used a classroom action research (CAR) which was conducted in two cycles in which every cycle consisted of four meetings. The location of this research was taken at the ninth grade students of SMP Muhammadiyah 5 Mariso, Makassar with a number of the subject were 36 students. The research findings indicated that the implementation of Mood Understand Recall Digest Expand and Review (MURDER) Strategy was improved the students’ reading comprehension in terms of literal comprehension and interpretive comprehension. It was proved by the mean score of cycle I was 64.31. It was classified as fair then improved to be 71.20. It was classified as fairly good in cycle II. They are higher than the mean score of diagnostic test 52.21 that classified as poor. Therefore there was improvement of the students’ reading comprehension in terms of literal comprehension dealing with main ideas and sequence of details and interpretive comprehension dealing with prediction of outcomes and conclusion.